Estudo da pirólise catalítica do bagaço de malte via micropirólise e leito de jorro: caracterização dos produtos e otimização do rendimento e da qualidade do bio-óleo - Santos, Grazielle Emanuella de Souza dos (2023)
The use of biomass has proven to be a viable alternative to the use of fossil fuels. Among the thermochemical conversion processes to obtain a product with higher added value, pyrolysis stands out due to the versatility of the obtained products. For this, the spouted bed reactor in the fast pyrolysis process, to optimize the production of bio-oil. However, the produced bio-oil usually presents in its composition several undesirable products and properties including high acid content, low calorific value and instability. Therefore, it is necessary to use catalysts to obtain a better-quality product to maximize hydrocarbon concentrations and minimize oxygenated compounds. So, this work aimed to evaluate the potential of brewer’s spent grain to generate fuels and chemicals of interest, through analytical pyrolysis (micropyrolysis) and fast pyrolysis in a spouted bed. The improvement of the bio-oil composition was investigated via catalytic micropyrolysis with catalysts based on calcium oxide and niobium oxide. The results obtained verified that the oxide-based catalysts had a greater influence on the partial deoxygenation of the vapors and on the increase in the yield of hydrocarbons, reaching levels of 38%. Also, the use of residues based on calcium oxide as catalysts has shown promise in the process of deoxygenation and increase of hydrocarbons. For the spouted bed pyrolysis tests, the response surface methodology was used. In the non-catalytic tests, the influence of temperature and feed flow rate on the liquid and solid yield and on the composition of hydrocarbons present in the bio-oil were evaluated. For the catalytic tests, the pyrolysis temperature and the catalyst concentration were evaluated. Non-catalytic and catalytic tests were studied through a Central Composite Design. It was observed that the yield of bio-oil, for non-catalytic tests, is favored under intermediate conditions of temperature (550°C) and feed flow (960g/h). In addition, the yield was favored with the addition of catalyst in the pyrolysis process. The desirability function was used to identify the conditions of the independent variables that simultaneously maximize the liquid yield and its hydrocarbon content. The experimental test in the ideal condition showed a maximum net yield of 41% with a hydrocarbon content of 15%. For the catalytic tests, a maximum bio-oil yield of 43% was observed and an increase in the hydrocarbon content reached levels of 33%. In addition, the results of the bio-oil composition are promising due to the low water content and the increase of hydrocarbons with the addition of calcium oxide catalyst. By characterizing the solid product, it was observed that the generated biochars had characteristics consistent with those reported in the literature and close to mineral coals. In addition, the generated products had a higher calorific value when compared to in natura brewer’s spent grain, which implies a higher energy density in biochar and bio-oil. Thus, this study verified promising results for the use of brewer’s spent grain for the production of fuels by the pyrolysis process, as well as the potential of using oxide catalysts to improve the quality of the liquid product.